The Linear Optical Properties of Rhodamin110 Organic Dye Doped with Metal Nanoparticles (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:Laser dyes are unsaturated hydrocarbon compounds that have the advantage of having double or triple bonds coupled with carbon atom chains. This system benefits from light absorption in the visible range (200–700 nm) and the transmission spectrum of absorption in the visible rangeMaterials and Methods:This research has focused on the effect of Adding ethanol solution to rhodamine110 dye with different concentrations, the linear properties (permeability, absorbance) of Rhodamine110 dye were studied as it was dissolved in ethanol to prepare solutions with concentrations (0. 01, 0.03, 0.05) and at room temperatureResults:The absorbance A of Rhodamine110 dye with ethanol was calculated for the above concentrations, respectively, as well as and the transmittance T was calculated for the above concentrations, respectively, to obtain curves and rhodamine110 dyes were mixed with nanomaterials to improve the properties of the dyesConclusion:In this study, According to Beer-Lambert's rule, increasing the dye concentration will increase absorbance, which will raise the linear optical coefficients (refractive index and coefficient of absorption) for all produced samples. The probability of electronic transitions will definitely be affected by the type of solvent., and this has an impact on linear optical characteristics, particularly the positions and width of the absorption spectra. And the addition of nanomaterials added better improvements to the dye. The results showed that the highest linear properties appeared when the silver nanomaterials with rhodamine110 dye